Sustainable Supply Chain Management in LED Manufacturing: A Qualitative Case Study of Orenda Energies Private Limited, Pakistan. - Ali, Hassan (My University, 2026)
This thesis explores sustainable supply chain management practices of Orenda Energies Private Limited, a manufacturer of LED and SMD lighting that operates within the Allah Hoo Industrial Estate in Lahore, Pakistan. The research is inspired by three overlapping gaps in the current body of SSCM research: that the electrical manufacturing industry in Pakistan has not been dedicatedly studied, that systematic underrepresentation of domestically-oriented SME manufacturers in developing country SSCM research, and the methodological hegemony of survey-based quantitative designs that cannot generate the operational specificity that firm level SSCM analysis demands. The research will follow a qualitative single case study research design based on an interpretivist philosophical stance and an inductive research methodology. It was collected as primary data using the reflexive thematic analysis process of Braun and Clarke (2019) with five semi structured interviews with respondents representing the executive, technical, operational, and client-side functions of the firm. The theoretical framework is a combination of three complementary lenses: the Natural Resource Based View of Hart (1995), which explains the motivational logic behind the sustainability practice in a resource-constrained environment; the Nine R Hierarchy of Potting et al. (2017), which evaluates how deep the practices surrounding the circular economy are placed in a spectrum of resource value retention; and the Institutional Voids framework of Khanna and Palepu (2010), which explains the conditions in which structures are placed to shape SSCM decision-making in the Pakistani manufacturing environment. The thematic analysis resulted in four themes. The first established: Orenda has a hybrid energy infrastructure consisting of a 100KW grid supply, a 50KW solar generation, a 100KW diesel backup, and that recycles polymer at a blended rate of 30 percent across their product range, and engages in an informal inter-firm steel-for-cardboard exchange of materials placed across R2, R3, and R8 of the Nine R Hierarchy. The second determined that the stakeholders view these practices as creating the value of continuation in operations, cost competitiveness, and creation of ESG value to the B2B clients. The third found that barriers limiting the effectiveness of SSCM are structural and institutional, based on the financial, regulatory, information, and infrastructure gaps in Pakistan. The fourth one determined that the most consequential strategic pathway that could be adopted by the firm is that of formalisation of the existing informal practices. This discussion synthesises these findings into the Emergent Sustainability Formalisation Model, a three-stage theoretical framework that proposes that the development of SSCM in manufacturing SMEs in institutional void conditions follows a trajectory of cost-driven emergence through formalisation to strategic deepening. The seven strategic recommendations are made within the immediate, medium-term and long-term periods all based on the empirical evidence and the theoretical framework.
Keywords: sustainable development; supply chains; Pakistan; green economy; case study; Lahore; recycling; circular economy; industrial areas; enterprises; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master’s Programme in Industrial Engineering and Management